Quality of human capital and labor productivity: a case of Malaysia - Mohd Arshad, Mohd Nahar; Ab Malik, Zubaidah (International Islamic University Malaysia, 2015)
In this study, we investigate the impacts of human capital on labor productivity in Malaysia using panel data analysis. Central to the study are the magnitudes of human capital variables, represented by educational levels and health status, on labor productivity. The panel data employed covers 14 states in Malaysia, spanning from 2009 to 2012. Results of the study are estimated using the fixed effects generalized least squares (GLS) model. The results show that human capital quality (higher educational levels and better health status) is positively significant in improving the level of labor productivity in Malaysia. Our estimates also suggest that the impact of health on labor productivity is greater than the impact of education. Improvements in the quality of health and education are therefore crucial for Malaysia to achieve higher productivity growth.